Energy management of a hybrid system based on wind-solar power sources and bioethanol - Feroldi, Diego Hernán (2013)
This work presents an Energy Management Strategy (EMS) for a sustainable hybrid system. It is based on wind-solar energy and bioethanol. The bioethanol reformer produces hydrogen with sufficient quality to feed a PEM fuel cell system, which can supply the load together with the wind-solar sources. The new an concept consists on having multiple power sources to supply the load where the necessary heating for the bioethanol reforming reaction can be provided by the the wind-solar sources to enhance the efficiency of the hydrogen production. An optimal sizing methodology based on genetic algorithms to design this stand- alone system is proposed. The developed model allows testing the potentiality of the proposed EMS under different scenarios of load demands using historical climate data over a period of one year. Then, the system is tested using several load scenarios to validate the proposed methodology.